Dispersion and Coagulation of Droplets in Intersecting Sprays - Dohmann, Joachim (Chemical Engineering & Technology)
Using a basic model of the collision process, the major parameters which dominate the disintegration processes are discussed. The observed and described effect of secondary drop dispersion leads to an improvement of atomization and can be used to improve heat and mass transfer performance of technical equipment.